Periodization of the Development of Medical Education in the USA - Tetiana Horpinich (Pedagogical Discourse, 2018)
The article is devoted to the question of the periodization of the educational system in the USA, which is important for revealing its origins, internal regularities, scientific generalization in historical and pedagogical science. The aim of the given research is to identify the main periods and leading trends in the development of medical education in the United States.The general characteristics of the concepts of «periodization», «periodization criterion», «period» are determined. Different approaches to the problem of periodization of educational systems are analyzed. On the basis of the analysis of different approaches to the definition of criteria and the implementation of the periodization of individually studied phenomena, the main criteria for substantiation of the historical and pedagogical periodization of higher medical education development in the USA are established: the dominant scientific-pedagogical paradigm, within which higher medical education develops, and the nature of political, social and economic events in the country. On the basis of these criteria, main periods are characterized, which in turn include specific internal stages or sub-periods.The basis of the periodization according to the first criterion was a large-scale analytical study of medical education in the United States and Canada, which was called the Flexner Report and became the basis of radical reforms of American medical education. Thus, the pre-reform period was characterized by the «student» model of medical education, the large number of uncredited private medical schools, the lack of scientific research within the educational institutions, whereas the post-reform period presented a new paradigm of professional training for doctors, which included the academic excellence of education itself, the expansion of the scope of fundamental and natural disciplines studied by medical students, introduction of large-scale scientific research within educational institutions. On the basis of the second criterion for periodization, five periods are distinguished: pre-colonial, colonial, period of building national health care system, period of reforming system of medical education, development of medical education under the conditions of globalization. It is established that at each stage, the tasks were addressed to meet the educational needs of American society. Thus, within each period, the driving forces and specific trends are identified.